Ambient-air in situ fabrication of high-surface-area, superhydrophilic, and microporous few-layer activated graphene films by ultrafast ultraviolet laser for enhanced energy storage. (April 2022) - Liu, Huilong; Zheng, Yixin; Moon, Kyoung-Sik; Chen, Yun; Shi, Dachuang; Chen, Xin; Wong, Ching-Ping
Abstract: Microporous graphene-based (MPG) films have attracted tremendous attention in micro-energy storage devices due to their unique characteristics of high specific surface area (SSA), high flexibility and high conductivity. However, current fabrication technologies generally provide overall activation in the form of powder in the bulky tube furnace, and multi-stepped thin film forming process, hurdling their practical utilizations that require efficient, cost-effective and controllable methods for large-area MPG films. Herein, a one-step and scalable laser induction & activation technique is reported for in situ fabrication of decimeter-level few-layer MPG films by utilizing ultrafast ultraviolet laser as a mobile heat source acting on microstructured polyimide film coated with KOH in air, which enable directly regulating the activation area on a flexible substrate. The resulting laser-induced and activated graphene (LIAG) films have interconnected hierarchical porous structures containing ultra- (0.5–0.8 nm) and super-micropores ( 1.2 nm), high SSA (>1300 m 2 g −1 ), small amount of doped potassium ( 0.50 wt%), and super-hydrophilicity (maximum droplet spreading velocity reaches 424.7 mm s −1 ). With the well-balanced properties of SSA, heteroatom doping, bulk density, and crystalline size, the LIAG micro-supercapacitors with interdigital electrodes of 35 µm width gap achieve a maximum areal capacitance of 128.4 mF cm −2, which outperforms state-of-the-art laser-processed carbon-based micro-supercapacitors. Additionally, it achieves almost the highest comprehensive evaluation considering processing precision, efficiency, cost and environmental friendliness. The facile, efficient, binder-free fabricability and roll-to-roll process compatibility would provide a rapid route for high-performance flexible energy storage devices. Graphical Abstract: ga1 Highlights: Ultrafast UV laser induction & activation technique is first developed for nanopores etching and K doping in graphene. In-situ fabrication of high surface-area, superhydrophilic and microporous few-layer activated graphene film in air. Ultra- and super-micropores are constructed on macroporous graphene walls to form hierarchical porous structures. The capacitance of LIAG-based IMSCs outperforms reported laser-processed carbon-based IMSCs. LIAG electrode achieves almost the highest evaluation considering precision, efficiency, cost and environment.